General Principles in European Small Claims Procedure – How Far can Simplifications go? - Nunner-Krautgasser, Bettina; Anzenberger, Philipp (LeXonomica, 2012)
The European Small Claims Regulation has been offering an alternative proceeding for small claims litigation in cross-border cases for almost four years now. Along with several important procedural simplifications, however, came considerable restrictions regarding the principles of public and oral proceedings established in the European Convention on Human Rights and the Charter of Fundamental Rights of the European Union. Critics claim especially that the court’s power to omit any oral hearing in a Small Claims Procedure cannot fulfill the requirements of the Convention and the Charter. This question is going to be further investigated in the course of this paper. Before doing so, however, a rough overview of the scope, of some general principals and of the conduct of the European Small Claims Procedure shall be provided. Osnovna načela evropskega postopka v sporih majhnih vrednosti – kje so meje poenostavitve? Uredba o evropskem postopku v sporih majhne vrednosti že skoraj štiri leta ponuja alernativni postopek v čezmejnih sporih majhnih vrednosti. Poleg številnih pomembnih postopkovnih poenostavitev pa vendarle obstajajo znatne omejitve glede načela javnosti in ustnega postopka, kot je to predvideno v Evropski konvenciji o človekovih pravicah in v Listini o temeljnih pravicah Evropske unije. Kritiki zlasti menijo, da pristojnost sodišča po neupoštevanju kakršnegakoli ustnega zaslišanja v postopku o sporih majhne vrednosti ni v skladu z zahtevami omenjene Evropske konvencije in Listine. Avtorja se v prispevku ukvarjata predvsem s tem vprašanjem, prav tako pa tudi orišeta vsebino posameznih splošnih načel in delovanje evropskega postopka v sporih majhnih vrednosti.